A Magnetic Method of Estimating the Height of Some Buried Magnetic Bodies - A. S. Eve (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1931)
IN the spring of 1930, the question was raised as to the possibility of estimating the depth to which the pyrrhotite-nickel deposit at the Falconbridge mine extended in the earth. This body is 7500 ft. long, it dips at 80° to the north, and it is fairly straight with slight sinuosities. Dr. F. W. Lee suggested that it might be possible to solve the problem by measuring the vertical magnetic intensity, with a good magnetometer, both near the surface of the earth and also at a level a 'few feet higher in the air. The writer regarded this suggestion with some scepticism, but it was decided to put the scheme to a prac¬ tical test. In July, 1930, Dr. Lee, Dr. Keys and I ' the writer, with Mr. Joyce and Mr. Belloc as assist¬ ants, made a firm, light wooden platform (Fig. 1) E measuring 4 by 4 ft. on the top, which was 10 ft. above ground. This platform could be moved easily a few yards by four men, and carried across I country in a wagon or by motor truck. Some iron nails were used in its construction, but we were not able to detect their influence on the - Askania magnetometer. Nevertheless, in future work, the use of iron should be completely avoided. Readings were taken along a traverse at right L angles to the orebody, at several stations, both on FIG. 1.-VERTICAL the ground and on the platform. The excess read- ASKANIA MAGNETOM¬ ETER ings, over the dike, as compared with those about 10 ETER ON A FT. HIGH. PLATFORM 800 ft. away, are shown in Table 1. The largest reading, 6.8, is open to suspicion and should be rejected. The depth of the top of the orebody is known by electrical survey, and by actual drilling, to be about 112 to 123 ft., and the covering is sandy glacial drift. Similar readings were taken over a long straight magnetic diabase dike. These also are shown in Table 1. The magnetic vertical intensity is consistently less at the higher level, which is l0 ft. above the lower level.